Relationship between principals’ leadership styles and motivation among support staff in public secondary schools in Nyamira County, Kenya. - Nyaboga, Nyagaka Evans; Bosire, Joseph N. (International Journal of Education and Research, 2015)
Secondary school support staffs are less satisfied with their posts in general, their contracts and conditions of employment, working arrangements for their post, training and development opportunities available to them are always demoralizing them. Going by the foresaid conditions of work, this study was set to determine the relationship between the principals’ leadership styles and motivation among support staff in public secondary schools in Nyamira County, Kenya. The specific objective of the study was to determine leadership styles used by principals to manage support staff in public secondary schools. The study adopted a descriptive survey design. The study population consisted of 170 public secondary schools, 170 principals, 172 deputy principals and 170 BOM chairpersons with 1020 support staff, totaling to 1532. Simple random and stratified sampling techniques were used to select 16 secondary schools, out of which one principal, six support staff, one deputy principal and the BOM chairperson from each of the sampled schools were selected, making a total sample of 144 respondents for the study. The findings revealed that leadership styles were interchangeably used on support staff depending on situations and circumstances. The study recommended that principals should be trained on various leadership styles and when to apply each style when managing support staff.
Keywords: Leadership styles; Public Secondary School; Staff Motivation; Support Staff